Suitability of Indian Hot-Rolled Parallel Flange Sections for Use in Seismic Steel Moment Resisting Frames - Ajay, Kulkarni Swati; Gaurang R, Vesmawala (International Journal of Sustainable Construction Engineering and Technology, 2012)
Use of parallel flange I beam sections is advantageous than tapered flange I beam sections due to, increased lateral stiffness, sections do not have sloping flanges and excessive material in web and easy to weld and bolt. Nowadays the hot rolled parallel flange, narrow parallel flange beams (NPB) and wide parallel flange beams (WPB) sections as per Indian standards, having yield stress, 300 MPa, 350 MPa and 410 MPa are being manufactured. Available range of these sections can be used for steel moment resisting frames (SMRF’s) and prequalified connections as per AISC codes. When the cross section of a steel shape is subjected to large compressive stresses, the thin plates that make up the cross section may buckle before the full strength of the member is attained if the thin plates are too slender. This failure mode may be prevented by selecting suitable width-to-thickness ratios of component plates. In the present exercise, a suitability of NPB and WPB section for use in SMRF’s as per width-to-thickness limitations of AISC 341-2010 and AISC 341-2005 codal provisions is studied.